Triboelectric charging of dust particles during hand-held circular sawing of wood and wood-based materials. Issue 1 (2nd January 2021) - Myna, Roman; Wimmer, Rupert; Liebner, Falk; Leiter, Lena; Frömel-Frybort, Stephan
ABSTRACT: During machining, wood particles are generated, released, and accelerated at high speed. Wood dust is known to be unpleasant, causing technical problems, but bears also considerable health risks. Wood dust consists of fractured tissues and has a high, irregularly structured surface due to tiny hooks formed by abundant sticking out fibrillar fragments. Targeting at a novel approach for dust reduction, this communication investigates triboelectric charging of wood particles upon cutting of wood samples using a hand-guided miter saw. The impact of wood species, number of saw blade teeth, cutting direction, and wood moisture, on electric field strength levels and polarity of generated wood particles were measured, using a electrostatic detection apparatus. The generated wood particles have shown accumulated triboelectric charging, as indicated by electric field strengths, which varied between −4 and +10 V m −1 . The intensity of the charge transfer was inversely proportional to the moisture content, especially when cut cross-sectionally. Highest field strengths were observed for beech, cut perpendicular to grain. Even though being a highly undesired effect, triboelectric charging of wood bears a novel opportunity for reducing the current dust burden in home and industrial wood processing environments, which is subject of ongoing and future research.